Assessing school happiness: Development and validation of a measurement scale for parents/guardians - Gramaxo, P.; Dias, Á.; Abelha, M.; Dutschke, G.; Seabra, F. (Frontiers in Education, 2025)
Introduction: Parents are one of the stakeholders in evaluating schools, and families’ perspectives about schools are increasingly acknowledged as essential to educational decision-making. However, little is known about how parents’ perspectives on school happiness can be assessed. This article proposes a model for evaluating school happiness as perceived by parents/guardians. Methods: Data were obtained through questionnaires administered to 641 parents. The model was tested using structural equation modeling techniques. Results: The results identified four main components: relationships and teachers’ characteristics (People), teaching practice (Process), learning/leisure balance (Process), and green school (Place). Discussion: The article discusses the development and validation of an instrument that can be used with parents/caretakers as one of the means of assessing a school’s overall happiness level and identifying key aspects to improve a school’s level of happiness. Implications for future research on the evaluation of happy schools are also discussed.